IMPLEMENTASI ODOO ERP UNTUK MENDUKUNG SUPPLY CHAIN MANAGEMENT (SCM) PADA BENGKEL AAC MOTORS - Satria; Celine Vidiana Mukti; Rudi Budi Agung; Marhakim; Widiyawati (Jurnal Teknologi Informasi dan Digital, 2024)
One important strategy used to increase the efficiency of ongoing business processes is by using applications that can integrate all departments and their functions, known as Enterprise Resource Planning (ERP). AAC Motors Workshop is a business operating in the automotive sector and still relies on conventional business system activities such as bookkeeping and recording reports manually. So, owners often experience difficulties when they need to report data on incoming and outgoing goods, and there are often discrepancies in the amount of goods data in the records with the existing physical stock. This puts additional pressure on the supply chain (supply chain management) on business processes, where this pressure is not a current target, but is dynamic and continuous. By using Odoo ERP to implement supply chain management (SCM), it can provide a solution to problems experienced in the company's business process activities, purchasing admins who can monitor the AAC Motors workshop business can easily control, schedule and collect product inventory data more efficiently. Rapid application development (RAD) is a method or model of software development process with a short, short and fast development cycle so that this method is suitable for implementing Odoo ERP at the AAC Motors workshop.